Penerapan Pendekatan Communicative Language untuk Meningkatkan Hasil Belajar Materi Bercerita Berdasarkan Teks Non Fiksi - Yoeni Indriati (Journal on Education, 2021)
For more than a year, elementary students have been required to study online from home or through the distance learning system (PJJ). Basically, the online learning system can be applied at various levels of education, from kindergarten to lectures. It's just that there needs to be a different emphasis and attention at each level. Basically, elementary school age students in small classes need more interaction with their environment. Therefore, a good blended-learning system is needed so that the usefulness of the assignments received by students and learning objectives can be achieved maximally. This study explores the problem of the low learning outcomes of Storytelling based on Non-Fiction Texts experienced by 3rd grade students of SD Negeri Sidotopo I/48 Surabaya. This study aims to determine whether or not there is an increase and how much increase in learning outcomes of storytelling based on non-fiction texts through the application of Communicative Language in 3rd grade students of SD Negeri Sidotopo I/48 Surabaya. Action research was carried out in two learning cycles by applying the Communicative Language Approach and student learning outcomes on storytelling material based on non-fiction texts as the object of research. Based on the explanation of the results of the research and discussion, it can be concluded that there is an increase in the learning outcomes of Storytelling based on Non-Fiction Texts through the application of the Communicative Language Approach to the 3rd grade students of SD Negeri Sidotopo I/48 Surabaya.